Isotherms, kinetics, and thermodynamics of boron adsorption on fibrous polymeric chelator containing glycidol moiety optimized with response surface method - Afolabi, H.K. (Elsevier B.V., 2021)
A fibrous boron chelator containing glycidol moiety (PE/PP-g-PVAm-G) was prepared by radiation induced grafting of N-vinylformamide (NVF) onto polyethylene/polypropylene (PE/PP) non-woven sheet followed by hydrolysis and immobilization of glycidol moiety. The glycidol density was controlled by optimization of the reaction parameters using the Box-Behnken design of response surface methodology (RSM). The properties of the PE/PP-g-PVAm-G were evaluated using Fourier transform infrared (FTIR) spectroscopy, field emission scanning electron microscopy (FESEM) and energy dispersive x-ray (EDX) analysis, X-ray diffraction (XRD) and thermal gravimetric analysis (TGA). A maximum glycidol density yield of 5.0 mmolÂ·gâ1 was obtained with 11.8 vol, 78.9 Â°C and 109.4 min for glycidol concentration, reaction temperature and time, respectively. The isotherms, kinetics, and thermodynamic behavior of boron adsorption on the optimized chelator were investigated. The boron adsorption was pH-dependent and attained a maximum adsorption capacity of 25.7 mgÂ·gâ1. The equilibrium isotherm proceeded by RedlichâPeterson model whereas the kinetics was best expressed by the pseudo-second-order equation. The thermodynamic analysis revealed that boron adsorption is endothermic and spontaneous. The fibrous chelator demonstrated high boron selectivity and strong resistance to foreign ions with uncompromised regeneration efficiency after five adsorption/desorption cycles. The PE/PP-g-PVAm-G chelator seems to be very promising for boron removal from aqueous media. Â© 2021 The Author(s)